MiR-29b-3p Inhibits Migration and Invasion of Papillary Thyroid Carcinoma by Downregulating COL1A1 and COL5A1 - Wang, Congjun; Wang, Ye; Fu, Zhao; Huang, Weijia; Yu, Zhu; Wang, Jiancheng; Zheng, Kaitian; Zhang, Siwen; Li, Shen; Chen, Junqiang (Frontiers in Oncology, 2022)
Introduction: MiRNAs are sncRNA molecules regulating genetic expression, and it's vital for tumor initiation and development. MicroRNA (miR)-29b-3p was involved in regulating various biological processes of tumors, including tumour cell proliferation, metastasis, and apoptosis inhibition, However, the biofunction and molecule-level mechanisms of miR-29b-3p in papillary thyroid carcinoma (PTC) remain unclear. Methods: The expression of miR-29b-3p in PTC samples was tested via qRT-PCR, Cellular proliferation was evaluated using CCK-8 and EdU analysis, cellular migratory and invasive abilities were assessed using wound healing and transwell assays. Protein expressions of COL1A1, COL5A1, E-cadherin, N-cadherin, Snail, and Vimentin were identified via WB assay. Bioinformatics, qRT- PCR, WB, and luciferase analysis were completed to identify whether miR-29b-3p targeted COL1A1 and COL5A1. In addition, our team explored the treatment effects of miR-29b-3p on a murine heterograft model. Results: Our findings revealed that miR-29b-3p was remarkably regulated downward in PTC tissue specimens than in adjacent non-cancerous tissues. Decreased expression of miR-29b-3p was strongly related to the TNM stage of PTC patients (P＜0.001). Overexpression of miR-29b-3p in PTC cells suppressed cellular migration, invasion, proliferation, and EMT. Conversely, silencing miR-29b-3p yields the opposite effect. COL1A1 and COL5A1 were affirmed as the target of miR-29b-3p. Additionally, the COL1A1 and COL5A1 were remarkably expressed in PTC tumor samples in contrast to neighboring healthy samples. Functional assays revealed that over-expression of COL1A1 or COL5A1 reversed the suppressive role of miR-29b-3p in migration, invasion, and EMT of PTC cells. Finally, miR-29b-3p agomir treatment dramatically inhibited Xenograft tumor growth in the animal model. Conclusions: The outcomes herein reveal a vital effect of miR-29b-3p on the proliferation, migration of PTC oncocytes, and the treatment value of such miRNA in PTC.